Artificial intelligence for audit, forensic accounting, and valuation : a strategic perspective - Naqvi, Ali S., 1968- (John Wiley & Sons, Inc., 2020)
"With significant and disruptive automation underway, accounting and auditing professions must rediscover themselves. The automation is permanently changing how services are developed and delivered. Due to the advent of highly cost-effective automated models that greatly outperform traditional auditing and forensic accounting, customers are demanding audit and accounting firms to automate. In this unsettling world dominated by "creative destruction", only those firms and professionals will survive and thrive who know how to adapt and innovate. At the center of all innovation are two revolutionary technologies: artificial intelligence and blockchain. The rise of artificial intelligence technology provides limitless opportunities for those who know how to adapt. Firms need a comprehensive framework for intelligent automation centric modernization. This book delivers a comprehensive framework to transform legacy firms into modern accounting and audit services firms. It provides a big picture view of building firmwide capabilities using artificial intelligence and empowers professionals by explaining: How artificial intelligence is the most important competitive advantage of modern audit and accounting firms. What is artificial intelligence and how it is being used in the industry How to compete effectively in the new age of accounting and audit. How to build your firm around artificial intelligence What are the governance challenges of AI How to deliver results with artificial intelligence"--